2012
DOI: 10.1080/14697688.2010.488654
|View full text |Cite
|
Sign up to set email alerts
|

Time-varying long-run mean of commodity prices and the modeling of futures term structures

Abstract: The exploitation of the mean-reversion of commodity prices is important for inventory management, in ‡ation forecasting and contingent claim pricing. Bessembinder, Coughenour, Seguin and Smoller (1995) document the mean-reversion of commodity spot prices using futures term structure data; however, mean-reversion to a constant level is rejected in nearly all studies using historical spot price time series. This indicates that the spot prices revert to a stochastic long-run mean. By recognizing this, I propose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…This implies that risk premium is time-varying and negatively correlated with the spot price. This result is also shown in and Tang (2012). 7 The risk of regime shift reveals some interesting results.…”
Section: Resultssupporting
confidence: 57%
“…This implies that risk premium is time-varying and negatively correlated with the spot price. This result is also shown in and Tang (2012). 7 The risk of regime shift reveals some interesting results.…”
Section: Resultssupporting
confidence: 57%
“…While the stochastic trend SSM also accounts for the price dynamics in the observed prices on the natural gas market it is not able to fully capture all the serial dependence of the coffee, cotton and aluminum prices. This is similar to the results of financial approaches on modeling commodity term structures, showing the relevance of additional pricing factors beyond the traditional ones for the spot price and the convenience yield (Miltersen and Schwartz 1998;Schwartz 1997;Tang 2012). The stochastic trend SSM is essentially a two-factor model with one reduced-form random walk component orthogonally appended to a factor restricted by economic constraints.…”
Section: Discussionsupporting
confidence: 81%
“…However, some sectoral studies do exist. For example, Marshall et al (2002) -in their analysis of long-term price as a function of copper consumption growth rate, future production, and profitability established for mining projects -found evidence of heterogeneous effects at the domestic level and demonstrated that long-term variations have a direct influence on the investment strategies of copper companies; Cuddington and Jerrett (2008) used band-pass filters to extract particular cyclical components from copper price series data, and found that high and low price rally cycles may inform public budgetary adjustments; and finally, Tang (2012) proposed a reduced-form model of the stochastic long-run mean as a separate factor in order to explore the mean reversion of copper price, to generate long-term budgets for public and private agents, and to inform investment decisions.…”
Section: International Price Of Commodities: Forecasting and Long-term Adjustmentsmentioning
confidence: 99%